Proses Pembuatan Program Ngasuh (Ngaji Bersama Pengasuh) Di Youtube Sebagai Media Penyebaran Informasi Islam - Rio Ferdinand Yofi; R. Hiru Muhammad (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Al-Hamidiyah Depok Islamic Foundation is one of the educational institutions that uses YouTube social media as a medium for disseminating information. The NGASUH (Ngaji Bersama Pengasuh) program premiered on March 14, 2022 until this thesis was made, it has reached 49 episodes. The obstacles faced such as technical constraints and the host cannot attend live broadcasts. This research aims to find out the process of making the NGASUH program through the YouTube social media of the Al-Hamidiyah Islamic Foundation as a means of disseminating Islamic information for students, teachers, employees at the Al-Hamidiyah Islamic Foundation and to find out what obstacles were faced during the process of making the NGASUH program through the YouTube social media of the Al-Hamidiyah Islamic Foundation. The research theory in this study is production theory which consists of pre-production, production, and post-production. This research methodology uses a qualitative approach with descriptive methods with data collection techniques are in-depth interviews. The pre-production of the NGASUH program is the initial stage in the event production process which involves planning, preparing, and organizing all the necessary aspects before the live broadcast is carried out. The production stage of a live program requires tight coordination, adaptability, and readiness to handle situations that may arise during the broadcast. The entire production team must work together to ensure the smooth running of the event and provide a good experience to the audience. The post-production phase of a live program is the phase after the live broadcast is completed, where the evaluation, processing, and distribution of the broadcast results are carried out. This stage is important to evaluate the quality of the broadcast, collect feedback, and conduct follow-ups based on the results of the broadcast such as storing the broadcast materials properly for future reference and archives.